1997
DOI: 10.1016/s0376-0421(97)00006-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of helicopter blade-vortex interaction noise by active rotor control technology

Abstract: Helicopter blade-vortex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…The development and behaviour of wind turbine wakes has been the focus of many investigations (Espana et al, 2012;Grant et al, 2000;Whale et al, 2000). In addition, investigations by Yu et al (1997), Yu (2000) and Beaumier and Delrieux (2005) have shown that tip vortices shed from helicopter rotor blades can induce unsteady pressure fluctuations on following blades, which cause unwanted vibrations and aerodynamic noise. The interaction of the wake with the blade, which is known as blade-vortex interaction (BVI) has a significant effect on the aerodynamics and structural dynamics of a helicopter rotor system.…”
Section: The Importance and Applications Of Wingtip Vorticesmentioning
confidence: 99%
“…The development and behaviour of wind turbine wakes has been the focus of many investigations (Espana et al, 2012;Grant et al, 2000;Whale et al, 2000). In addition, investigations by Yu et al (1997), Yu (2000) and Beaumier and Delrieux (2005) have shown that tip vortices shed from helicopter rotor blades can induce unsteady pressure fluctuations on following blades, which cause unwanted vibrations and aerodynamic noise. The interaction of the wake with the blade, which is known as blade-vortex interaction (BVI) has a significant effect on the aerodynamics and structural dynamics of a helicopter rotor system.…”
Section: The Importance and Applications Of Wingtip Vorticesmentioning
confidence: 99%
“…Noise generated by the helicopter blade comes mainly from the interaction between one blade and the vortexes generated by the previous blade [69]. This phenomenon is called blade-vortex interaction (BVI).…”
Section: Active Trailing Edge Flapsmentioning
confidence: 99%
“…Decreasing the effects of blade-vortex interaction can not only lead to a reduction in the noise emitted but also to a decrease in the power requirement. Active trailing edge flaps are actively studied to limit this effect by an individual control on each blade [1,18,69]. Controlling the trailing edge flap at 2 cycles per revolution (hereafter indicated as 2/rev) shows potential for consequent noise reduction [1].…”
Section: Active Trailing Edge Flapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches based on higher harmonic blade control have been investigated in detail, both numerically and experimentally in the past literature. [2][3][4][5] Specifically, the attention has focused mainly on two types of control systems: the individual blade control (IBC), for which each blade is controlled in the rotating frame through pitch links or flaps, and the so-called higher harmonic control (HHC), which acts on all the blades simultaneously by driving the non-rotating component of the swashplate. The benefits of HHC and IBC in reducing both vibrations and acoustic annoyance have been widely discussed, although some drawbacks emerged.…”
Section: Introductionmentioning
confidence: 99%